Determinant Of Purchase Decision, Study Case: PT. Unilever Indonesia - Irham Amir; Renaldi Septiawan (FORBISWIRA FORUM BISNIS DAN KEWIRAUSAHAAN, 2023)
The process of offering products to consumers has begun to develop along with the development oftechnology. A proper marketing strategy is the main key to make a business performed well in accordance withcompany expectation. Digital marketing has been widely used by entrepreneur in their business activities to improvetheir company performance. Meanwhile product quality is one of consumers’ consideration in purchasing aproduct. When consumers are interested to consume a certain product, they will most likely make a decision topurchase it. This research aims to find out the influence of digital marketing and product quality on purchasedecisions using multiple linear regression analysis methods. The respondents are 100 consumers of Unilever productsin Bogor Regency with Cluster Random Sampling technique. By implementing a multiple linear regressionmodel, the study revealed that both digital marketing and product quality affects purchase decisions partially andsimultaneously